Combined sequence and copy number analysis improves diagnosis of limb girdle and other myopathies - Babi R. R. Nallamilli; Yinghong Pan; Lisa Sniderman King; Lakshmanan Jagannathan; Vinish Ramachander; Ann Lucas; Jan Markind; Raffaella Colzani; Madhuri Hegde (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Clinical and genetic heterogeneities make diagnosis of limb‐girdle muscular dystrophy (LGMD) and other overlapping disorders of muscle weakness complicated and expensive. We aimed to develop a comprehensive next generation sequence‐based multi‐gene panel (“The Lantern Focused Neuromuscular Panel”) to detect both sequence variants and copy number variants in one assay. Methods Patients with clinical diagnosis of LGMD or other overlapping muscular dystrophies in the United States were tested by PerkinElmer Genomics in 2018–2021 via “The Lantern Project,” a sponsored diagnostic testing program. Sixty‐six genes related to LGMD subtypes‐ and other myopathies were investigated. Main outcomes were diagnostic yield, gene‐variant spectrum, and LGMD subtypes' prevalence. Results Molecular diagnosis was established in 19.6% (1266) of 6473 cases. Major genes contributing to LGMD were identified including CAPN3 (5.4%, 68), DYSF (4.0%, 51), GAA (3.7%, 47), ANO5 (3.6%, 45), and FKRP (2.7%, 34). Genes of other overlapping MD subtypes identified included PABPN1 (10.5%, 133), VCP (2.2%, 28), MYOT (1.2% 15), LDB3 (1.0%, 13), COL6A1 (1.5%, 19), FLNC (1.1%, 14), and DNAJB6 (0.8%, 10). Different sizes of copy number variants including single exon, multi‐exon, and whole genes were identified in 7.5% (95) cases in genes including DMD, EMD, CAPN3, ANO5, SGCG, COL6A2, DOK7, and LAMA2. Interpretation “The Lantern Focused Neuromuscular Panel” enables identification of LGMD subtypes and other myopathies with overlapping clinical features. Prevalence of some MD subtypes was higher than previously reported. Widespread deployment of this comprehensive NGS panel has the potential to ensure early, accurate diagnosis as well as re‐define MD epidemiology.